Profile and Pattern of Women Seeking Medical Termination of Pregnancy in a Tertiary care Centre in National Capital Region - Ankita Kakkar; Pooja Rastogi; Anshul Saxena; Sushil Kumar; Alok Kumar (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: Induced abortion whether safe or unsafe, legal or illegal is a reproductive health service thatis part of the lives of women, couples and communities all over the country. When faced with unintendedpregnancies, especially in contexts in which women lack access to effective family planning, inducedabortion is an important part of women’s reproductive health care. In this backdrop the present study wasundertaken with the objective to study socio-demographic profile, methods, various indications in MedicalTermination of Pregnancy cases performed in our institution.Method: This study was conducted in the Department of Forensic Medicine in collaboration withDepartment of Obstetrics and Gynaecology, at SMSR, GautambudhNagar, India. Information was obtainedfrom the patient seeking abortion services, patient’s case record file in the hospital, Medical Terminationof Pregnancy (MTP) register and direct interview with concerned consultant in charge in the form of predesigned questionnaire..Conclusion: The most common reason for MTP was unwanted pregnancy due to non use of contraceptivesby the women of reproductive age group. We recommend comprehensive contraceptive counseling canhelp prevent unintended pregnancies that lead to abortions and should include information on when fertilityreturns after a birth or abortion. Also dedicating a special cell to focus on a woman’s unmet needs ofcontraception would go a long way in resolution of unintended pregnancies and abortions.